Small scale irrigation interventions for system productivity and natural resource management in Ethiopian highlands: benefits and best-bets - Amede, Tilahun; Gebre-Mariam, A.; Felloni, F. (2008)
Water scarcity became a common phenomenon in Ethiopia with drought frequency of at least once in three years while the country owns a large irrigation potential that should be exploited sustainably. Various national and international institutions are currently engaged in developing small scale irrigation (SSI) schemes for poverty alleviation. A monitoring and evaluation exercise was conducted in 2004 and in 2006 in four administrative regions of Ethiopia, namely Tigray, Southern regions, Oromia and Amhara, to assess the benefits and associated environmental effects of SSI investments of the International Fund for Agricultural Development (IFAD). A combination of participatory M&E tools namely, individual interviews, group discussions, key informants, review of relevant documents and field observations were used. The mission was supported by an in depth pre-mission socio-economic survey in three representative irrigation schemes. Data from the sites indicated that 50 % of the respondents had improved food security and higher income, while 26% of the respondents did not see any change on their livelihoods. Crop yield under irrigation was by 35% to 200% higher than under rain fed conditions, with much higher benefit obtained from high potential areas and in farms where external inputs (fertilizer, improved seeds and pesticides) are accessible. The positive effect was more visible with horticultural crops. There has been also a shift towards improved varieties with access to irrigation. Farmers replaced early maturing but low yielding varieties with high yielding varieties. Crop diversification increased significantly, in some sites from three to about 15 species, although this decision making process did not favour legumes. The apparent effect was on crop rotation, intercropping and land management with in the order of 79, 42 and 35%, respectively. On the other hand, there is a decline in number of livestock per household, but an increased number of draught oxen. The decline is associated with reduced grazing area due to conversion of dry season fallow to vegetable fields and an increase in area enclosure in the sloppy landscapes. The shift from cereal to vegetable-dominated cropping increased the competition for water between downstream and upstream users and between resource rich and poor farmers. The impact of irrigation schemes should be evaluated better on long term benefits than short term fixes, as farmers initiated long term investments like planting perennial fruits, bought calves and other retail trade investments. The communities would benefit most from further integration of livestock into the schemes by adopting feed sourcing strategies for dairy and fattening. The paper also presented best-bets for improved irrigation management in Ethiopia.